2008
DOI: 10.1136/hrt.2006.114306
|View full text |Cite
|
Sign up to set email alerts
|

Arterial haemodynamics in patients after repair of tetralogy of Fallot: influence on left ventricular after load and aortic dilatation

Abstract: These results indicating abnormal arterial haemodynamics after TOF repair highlight the importance of regular monitoring of the systemic arterial bed and potentially relevant cardiovascular events in long-term follow-up of TOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 35 publications
(48 reference statements)
6
50
0
Order By: Relevance
“…5,6,19 Indeed, a number of studies have reported increased aortic stiffness and its significant effect on aortic dilatation in these diseases. [7][8][9][10][11][12] In agreement with these previous observations, the present study adds new data showing that aortic medial pathology may also be implicated in the mechanism of aortic dilatation observed in patients with SiV physiology. The increased aortic stiffness observed in the present SiV patients is consistent with data from an important study by Niwa et al, who showed that abnormal aortic medial histopathology, characterized by elastic fiber disruption, was observed in patients with SiV physiology analogous to that of the present patients, including double-outlet right ventricle, single ventricle, or tricuspid atresia.…”
Section: Resultssupporting
confidence: 80%
“…5,6,19 Indeed, a number of studies have reported increased aortic stiffness and its significant effect on aortic dilatation in these diseases. [7][8][9][10][11][12] In agreement with these previous observations, the present study adds new data showing that aortic medial pathology may also be implicated in the mechanism of aortic dilatation observed in patients with SiV physiology. The increased aortic stiffness observed in the present SiV patients is consistent with data from an important study by Niwa et al, who showed that abnormal aortic medial histopathology, characterized by elastic fiber disruption, was observed in patients with SiV physiology analogous to that of the present patients, including double-outlet right ventricle, single ventricle, or tricuspid atresia.…”
Section: Resultssupporting
confidence: 80%
“…This is consistent with clinical data showing that direct measurements of PWV in children with TOF are worse compared with age-matched controls. 8,12 Other possible risk factors for aortic pathology may be more modifiable such as age at repair. Historically, the surgical approach in most centers often included an initial palliative shunt; definitive repair was performed later than in contemporary practice.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to Z c , arterial wave reflection is also a major determinant of the aortic pressure waveform, and short stature in infants may cause an early return of the reflected wave, which may augment the forward pressure wave [19]. However, younger age is associated with a compliant aortic wall, and this reduces pulse wave velocity [20,21], counteracting the effects of the short traveling pathway (distance between aorta and peripheral artery). Indeed, we did not observe any inflection point on the rapid upstroke of aortic pressure trajectory in any of the studied patients (as shown in Fig.…”
Section: Limitationsmentioning
confidence: 96%